The mental health toll among healthcare workers during the COVID‐19 Pandemic in Malawi - Maliwichi, Limbika; Kondowe, Fiskani; Chilungamo, M'manga; Mchenga, Martina; Kainja, Jimmy; Nyamali, Simunye; Ndasauka, Yamikani (Springer Nature, 2024)
The COVID-19 pandemic has affected the mental health of healthcare workers worldwide, with frontline personnel experiencing heightened rates of depression, anxiety, and posttraumatic stress. This mixed-methods study aimed to assess the mental health toll of COVID-19 on healthcare workers in Malawi. A cross-sectional survey utilising the Generalized Anxiety Disorder (GAD-7), Patient Health Questionnaire (PHQ-9), and Primary Care PTSD Screen for DSM-5 (PC-PTSD-5) was conducted among 109 frontline healthcare workers. Additionally, in-depth interviews were conducted with 16 healthcare workers to explore their experiences and challenges during the pandemic. The results indicated a high prevalence of COVID-19-related depression (31%; CI [23, 41]), anxiety (30%; CI [22, 40]), and PTSD (25%; CI [17, 34]) among participants. Regression analysis revealed significantly higher rates of depression, anxiety, and PTSD among healthcare workers in city referral hospitals compared to district hospitals. Qualitative findings highlighted the emotional distress, impact on work and personal life, and experiences of stigma and discrimination faced by healthcare workers. The stress process model provided a valuable framework for understanding the relationship among pandemic-related stressors, coping resources, and mental health outcomes. The findings underscore the urgent need for interventions and support systems to mitigate the mental health impact of COVID-19 on frontline healthcare workers in Malawi. Policymakers should prioritise the assessment and treatment of mental health problems among this critical workforce to maintain an effective pandemic response and build resilience for future crises.
Contributions L.M., Y.N., J.K., S.N., F.K., M.M., and C.M. conceptualised the idea and reviewed the manuscript. L.M., M.M., J.K., C.M. and F.K. analysed the data. L.M., Y.N., and F.K. drafted the paper. All authors contributed to the article and approved the submitted version. Corresponding author Correspondence to Yamikani Ndasauka.
Keywords: Depression; Anxiety; Post-traumatic stress disorder; COVID-19; Healthcare workers; Mixed methods; Stress process model; Malawi